From weak to strong interactions: structural and electron topology analysis of the continuum from the supramolecular chalcogen bonding to covalent bonds. Issue 14 (23rd March 2022) - Miller, Daniel K.; Chernyshov, Ivan Yu.; Torubaev, Yury V.; Rosokha, Sergiy V.
Abstract : Continuities of interatomic distances and characteristics of bond critical points demonstrate an intrinsic link between covalent and supramolecular bonding involving chalcogen atoms. Abstract : The relationship between covalent and supramolecular bonding, and the criteria of the assignments of different interactions were explored via the review of selenium and tellurium containing structures in the Cambridge Structural Database and their computational analysis using Quantum Theory of Atoms in Molecules (QTAIM). This combined study revealed continuums of the interatomic Se⋯Br and Te⋯I distances, d Ch⋯X, in the series of associations from the sums of the van der Waals radii of these atoms ( r Ch + r X ) to their covalent bond lengths. The electron densities, ρ ( r ), at Bond Critical Points (BCPs) along the chalcogen bond paths increased gradually from about 0.01 a.u. common for the non-covalent interactions to about 0.1 a.u. typical for the covalent bonds. The log  ρ ( r ) values fell on the same linear trend line when plotted against normalized interatomic distances, R XY = d Ch⋯X /( r Ch + r X ). The transition from the positive to negative values of the energy densities, H ( r ), at the BCPs (related to a changeover of essentially non-covalent into partially covalent interactions) were observed at R XY ≈ 0.80. Synchronous changes of bonding characteristics with R XY (similar to that found earlier in the halogen-bonded systems) designated normalized interatomic separation as a critical factor determining the nature of these bondings. The uninterrupted continuums of Te⋯I and Se⋯Br bond lengths and BCPs' characteristics signified an intrinsic link between limiting types of bonding involving chalcogen atoms and between covalent and supramolecular bonding in general.